2017
DOI: 10.1073/pnas.1708907114
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme stabilization via computationally guided protein stapling

Abstract: Thermostabilization represents a critical and often obligatory step toward enhancing the robustness of enzymes for organic synthesis and other applications. While directed evolution methods have provided valuable tools for this purpose, these protocols are laborious and time-consuming and typically require the accumulation of several mutations, potentially at the expense of catalytic function. Here, we report a minimally invasive strategy for enzyme stabilization that relies on the installation of genetically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 58 publications
6
78
0
Order By: Relevance
“…43 Fasan and co-workers showed that construction of an articial thioether bond between a non-natural amino acid of O-2-bromoethyl Tyr and Cys in Mb may increase $0.24 M for C m upon Gdn$HCl-induced unfolding. 57 Moreover, Hollenberg and co-workers constructed a de novo disulde bond close to the heme center in Cyt P450 2B1 by a double mutation of Y309C/ S360C, which reduced the protein plasticity and ne-tuned the metabolic activity. 58 These observations suggest that the location for engineering a covalent bond is crucial for the enhancement of stability, as well as functional regulation.…”
Section: Chemical-induced Unfolding Studiesmentioning
confidence: 99%
“…43 Fasan and co-workers showed that construction of an articial thioether bond between a non-natural amino acid of O-2-bromoethyl Tyr and Cys in Mb may increase $0.24 M for C m upon Gdn$HCl-induced unfolding. 57 Moreover, Hollenberg and co-workers constructed a de novo disulde bond close to the heme center in Cyt P450 2B1 by a double mutation of Y309C/ S360C, which reduced the protein plasticity and ne-tuned the metabolic activity. 58 These observations suggest that the location for engineering a covalent bond is crucial for the enhancement of stability, as well as functional regulation.…”
Section: Chemical-induced Unfolding Studiesmentioning
confidence: 99%
“…In the future, further advantage might be gained by engineering redox-stable disulfide analogs, such as has been explored in the case of sunflower trypsin inhibitor, a very small canonical inhibitor accessible through total synthesis (42,43). This type of engineering would require incorporation of stable cross-links into proteins through the use of genetically encoded, noncanonical amino acids (26,44). We predict that such disulfide-engineered proteins with enhanced stability could lead to the development of a new generation of biopharmaceuticals.…”
Section: Disulfide Engineering Of Kunitz Protease Inhibitorsmentioning
confidence: 99%
“…This is especially the case for heme protein design, which has received much attention in the last few decades, and various approaches have been established for rational design, such as the introduction of non-heme metal ions and unnatural amino acids, and the use of heme mimics to act as an active site [1][2][3][4][5][6][7][8][9][10][11][12]. Importantly, computer modeling and molecular dynamics (MD) simulation play key roles in guiding the protein design [13][14][15][16][17][18]. For example, computer simulation was successfully applied to design a non-heme iron binding site in the heme pocket of myoglobin (Mb), which converted an O 2 carrier into a functional nitric oxide reductase [19].…”
Section: Introductionmentioning
confidence: 99%